Changes in plant diversity patterns along dune zonation in south Atlantic European coasts. (5th March 2019) - Torca, Marta; Campos, Juan Antonio; Herrera, Mercedes
Abstract: Coastal dunes are valuable and threatened habitats. They present a sea-land environmental gradient and different vegetation types are found in a very short space: embryo, mobile and fixed dunes. The aims were to study changes in taxonomic diversity and species richness along the ecological gradient and if they were followed by changes in functional or phylogenetic diversity. This study took place along a 750 km coastal stretch, belonging to four biogeographic sectors, in the southwest of France and northwest of Spain. Twelve locations were selected, where coastal dune habitats were explored. In each location and for each vegetation type four 10 × 10 m plots were sampled. In each plot abundances of vascular plants were recorded. Taxonomic, functional and phylogenetic diversity at the alpha level were measured. NMDS analysis, PERMANOVA and linear mixed effects models were used to explore differences between biogeographic sectors and habitats for species composition and each derived taxonomic, functional and phylogenetic index. We found different species composition in each vegetation type: in embryo dunes it was constant along biogeographic sectors, while it changed in mobile and fixed dunes. Taxonomic diversity, functional diversity and phylogenetic diversity indices did not show changes at biogeographic sector level despite the species difference in mobile and fixed dunes. An increase in taxonomic diversity from embryo to fixed dunes was also found, followed by an increase in functional divergence. Phylogenetic diversity decreased from embryo to fixed dunes. Therefore, in habitats more exposed to sea, wind and waves, as embryo dunes, environmental filtering selects some traits of non-related species. On more sheltered habitats such as fixed dunes, biotic interactions like competitive exclusion leads to a divergence in functionality. In conclusion, coastal dunes showed different biodiversity patterns along a sea-land gradient; despite a difference in species, functional and phylogenetic diversity remained without changes along a geographical gradient. Graphical abstract: Image 1 Highlights: Species composition changes along sea-inland gradient. Taxonomic and functional diversity have higher values on fixed dunes. Phylogeny is less overdispersed from sea to land. Environmental filtering may influence communities next to sea. Biotic interactions such as competition and microclimate may play a major role inland.